Dairy farmer, engagement and understanding of One Health and antimicrobial resistance - a pilot survey from the lower north island of Aotearoa New Zealand. - Arden K; Rosanowski SM; Laven RA; Mueller KR (BioMed Central Ltd. Part of Springer Nature, 2024)
BACKGROUND: Reducing antimicrobial resistance (AMR) requires a multidisciplinary One Health approach, which necessitates buy-in from all stakeholders. In Aotearoa New Zealand, where the dairy industry is one of the largest users of antimicrobials, there are ongoing efforts to optimise antimicrobial usage (AMU) to minimise the development of AMR. These include regulations around the veterinary authorisation of the use of antibiotics by farmers without the need for a specific prescription ("the RVM process") and programmes such as the New Zealand Veterinary Association's antibiotic 'Traffic Light System'. The goal of this pilot survey was to develop and trial a questionnaire to determine how much Aotearoa dairy farmers understand about One Health, AMR, the RVM process and how their actions regarding AMU affect the wider environment. METHODS: A 55-question semi-structured questionnaire was piloted on 15 dairy farms in the Lower North Island of Aotearoa New Zealand via an in-person semi-structured interview between September and November 2021. RESULTS: None of the interviewed farmers could define the term One Health. However, the majority found the RVM process to be of use on their farm, although admitted they generally felt frustration regarding AMR, seeing it as a blockage to productivity, and lacked awareness regarding how their actions were related to its development. Of the farmers interviewed over half had not heard of the traffic light system, and of those who had, one admitted they refused to adhere to it. CONCLUSIONS: This survey's novel findings have highlighted that there are notable gaps within dairy farmer understanding of AMU, AMR and One Health as well as highlighting that veterinarians could do more to keep their clients informed of their important role within One Health. There is still a lot more work to do with regards to vets, farmers and industry representatives working together to embrace One Health. Simple solutions would be to encourage farmers returning unused drugs to their veterinarians for correct disposal and to actively engage farmers further regarding AMU and AMR, so that these end-product users do not feel disconnected from the process.
Keywords: Antimicrobial Resistance; Antimicrobial Usage; Aotearoa-New Zealand; Dairy Farmers; One Health